Enhanced near-infrared response of a silicon solar cell by using an up-conversion phosphor film of Yb/Er – co-doped CeO2. (1st September 2018) - Grigoroscuta, M.; Secu, M.; Trupina, L.; Enculescu, M.; Besleaga, C.; Pintilie, I.; Badica, P.
Highlights: Films of Ce0.95 Yb0.04 Er0.01 O2, were grown by PLD on a single crystal silicon diode. The up-conversion film grown for 2.3 J/cm 2 delivers the highest device performance. The relative power conversion efficiency of the device is 12.1/39.2% at 1/2.1 sun. The external quantum efficiency is 7.2% when illuminated with 980 nm light. Abstract: Co-doped CeO2 thin films were grown from a bulk target with starting composition Ce0.95 Yb0.04 Er0.01 O2 by pulsed laser deposition (PLD) on a p + -n-n + single crystal silicon diode. The PLD laser fluence was varied between 1.7 J/cm 2 and 3.7 J/cm 2 . The device with the film grown for a laser fluence of 2.3 J/cm 2 delivers the highest performance taking advantage of the up conversion (UC) effect provided by this film. Namely, the increase in the relative power conversion efficiency of the device is 12.1% and 39.2% for illumination under 1 and 2.1 sun, respectively, and its relative external quantum efficiency is 8.2% when illuminated with 980 nm light. The film grown for the optimum 2.3 J/cm 2 fluence shows good target-film composition transfer and a granular morphology with a low roughness. The UC mechanism consists of efficient energy transfer between spatially separated Yb 3+ and Er 3+ ions, i.e. the absorption of infrared light photons by the Yb 3+ ions ( 2 F 7/2  →  2 F 5/2 transition) is followed by a two-step energy transfer process to neighboring Er 3+ ions and by their characteristic luminescent emissions (( 2 H 11/2, 4 S 3/2 ) →  4 I 15/2 ) and ( 4 F 9/2  →  4 I 15/2 ).